ANALISIS MATIUS 6:25-34 “PENGAJARAN HAL KEKUATIRAN” MELALUI MODEL DIRECT INSTRUCTION DENGAN METODE CERAMAH - Sutrisno, Ribut Agung; Wulandari, Yulia Warih Her; Rianto, Viktoria Ayu (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This research aims to obtain objective information regarding the Analysis of Matthew 6:25-34 concerning teaching matters of concern through the direct instruction model with the lecture method. In this research, word study analysis and literature review of the text will be carried out in the hope of obtaining biblical knowledge about how to model direct instruction with the lecture method based on the book of Matthew 6:25-34 when teaching about concerns, so it can be concluded that the direct model instruction with the lecture method based on the book of Matthew 6:25-34 which the Lord Jesus did can provide examples of the lecture method with oral explanations in a systematic and attractive manner in front of many people so that the students who are taught can receive His teaching well.